Implementasi Teknologi Informasi dan Komunikasi (TIK) Dalam Meningkatkan Daya Saing Umkm - Vera Maria; Regi Regi; Hayanti Hayanti (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Information and Communication Technology (ICT) has emerged as a crucial determinant in business transformation, particularly for Micro, Small, and Medium Enterprises (MSMEs). This research aims to delve deeply into how the implementation of ICT in MSMEs contributes to enhancing their competitiveness. The research method employed is descriptive analysis with a qualitative approach, where data were collected through interviews with MSME owners who have implemented information technology in their operations.The results indicate that the integration of ICT has provided significant positive impacts on MSMEs. One of the key benefits is the enhancement of operational efficiency, where the use of information systems has expedited business processes and reduced operational costs. Additionally, MSMEs that adopt information technology also have broader market access through online platforms and social media, thereby enhancing sales potential and business growth. However, the implementation of ICT in MSMEs also faces several challenges, such as high implementation costs, limited access to infrastructure, and concerns about data security. Therefore, strong support from the government, non-governmental organizations, and the private sector is needed to provide training, technical assistance, and necessary infrastructure for MSMEs to harness the full potential of ICT.